Preparation method and application of graphene aerogel with multiple pore channels
Through step-by-step one-way freezing and high-temperature regeneration techniques, graphene aerogels with multiple pores were prepared, which solved the problem of single pore structure of existing materials and achieved efficient thermal insulation and photothermal adsorption effects.
Patent Information
- Application Number
- CN202411821074.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing graphene aerogel materials have a single pore structure, thick pore walls and low porosity, which limits their promotion in the field of adsorbents and their application in energy conservation.
By mixing the aqueous graphene oxide dispersion with oil, performing high-speed shearing, step-by-step one-way freezing, combined with vacuum drying and high-temperature reduction, graphene aerogel with multiple pores was prepared.
The prepared graphene aerogel has high porosity and anisotropic thermal conductivity. It can not only achieve energy saving in the field of insulation, but also quickly recover crude oil in the field of photothermal adsorption, and has a wide range of application prospects.
Smart Images

Figure CN119430168A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation and adsorption materials, and in particular to a method for preparing a graphene aerogel with multiple pores for use in the fields of thermal insulation and oil spill treatment. Background Art
[0002] With the development of the global economy and the increase in population, the demand for energy in various fields such as industrial production, urbanization, transportation, agriculture and residents' lives is constantly increasing. Traditional energy resources such as coal, oil and natural gas are limited resources with limited reserves and are non-renewable. With the exploitation and consumption of these traditional energy resources, their supply is gradually decreasing and becoming increasingly difficult to obtain. Energy supply is affected by a variety of factors including natural disasters and man-made accidents, resulting in interruptions or instability in energy supply, further exacerbating the problem of energy shortage. This is why we need to advocate energy conservation and recycling. Energy reduction is a real problem, and it is imperative to take positive measures such as developing renewable energy, improving energy utilization efficiency, promoting energy-saving technologies and strengthening energy management to meet the challenges of the energy crisis.
[0003] Thermal insulation materials and adsorbent materials play an important role in the field of energy conservation and recycling. Thermal insulation materials play an irreplaceable role in energy conservation and are widely used in the fields of construction, industrial equipment and pipelines. Thermal insulation materials can reduce the heat exchange inside and outside buildings and devices, slow down the heat transfer rate, reduce heat loss, reduce the load of the heating system, improve energy utilization efficiency, thereby saving energy and reducing energy costs. In addition, the exploitation, transportation and utilization of oil resources have led to frequent oil leaks, which not only pose a huge threat to the ecological environment, but also consume a large amount of energy, causing huge losses to society and the economy. Adsorbent materials are of great significance for the recovery of leaked oil. For example, in an offshore crude oil spill accident, as the light components in the crude oil volatilize and the heavy components remain, the viscosity of the crude oil increases significantly and the fluidity decreases, making it extremely difficult to handle. The viscosity of crude oil will decrease significantly with the increase in temperature. Therefore, it is a feasible idea to develop an adsorbent material to reduce the viscosity of crude oil by heating it, and then treat the leaked crude oil.
[0004] Graphene is a sp 2A two-dimensional carbon material with a honeycomb lattice structure connected to each other in a hybrid manner, with stable chemical properties and good thermal conductivity. Aerogel is a porous material with low thermal conductivity and high specific surface area. Graphene aerogel has most of the advantages of graphene and aerogel, and is widely used in the fields of thermal insulation and adsorption. For example, Chen Lijun et al. prepared graphene aerogel fibers (graphene aerogel fibers, graphene aerogel insulation flakes and preparation methods thereof, CN114717688A) by wet spinning, reducing, and supercritical carbon dioxide drying of graphene oxide liquid crystals. The material has the advantages of high gas heat conduction suppression efficiency and low thermal conductivity, and has good thermal insulation performance, but the material has a small pore size, which limits its promotion in the field of adsorbents. Zhang Hailong et al. (A method for preparing graphene aerogel with adjustable pore size, CN109133040A) used ice crystals as templates to prepare graphene aerogel with precisely adjustable pore size by reduction freezing method from graphene oxide suspension. This method can precisely control the pore size by controlling the freezing temperature and speed. However, the graphene aerogel prepared by this method has a single pore structure, thick pore wall, low porosity, and insufficient pore richness per unit mass of the material.
[0005] Therefore, the development of graphene aerogels with unique pore structure and simple preparation process is of great significance for achieving large-scale energy conservation and resource recycling. Summary of the invention
[0006] In order to solve the deficiencies in the prior art, the present invention provides a method for preparing a graphene aerogel with multiple pores and its application to solve the problems in the prior art. The present invention performs step-by-step unidirectional freezing on an unstable water-in-oil emulsion, and prepares a graphene aerogel with multiple pores after vacuum drying and high-temperature reduction. The prepared material has extremely high porosity and anisotropic thermal conductivity, which can be used in the field of thermal insulation to achieve energy conservation, and can also be used in the field of photothermal adsorption to achieve rapid recovery of crude oil and effective utilization of energy.
[0007] The present invention adopts the following technical solution.
[0008] The first aspect of the present invention discloses a method for preparing a graphene aerogel having multiple pores, comprising the following steps:
[0009] The graphene oxide aqueous dispersion and the oil phase are mixed according to a set volume ratio, and an unstable oil-in-water emulsion is obtained after high-speed shearing;
[0010] The obtained oil-in-water emulsion is subjected to step-by-step unidirectional freezing to obtain a graphene oxide solid hydrogel through step-by-step solidification of water and oil;
[0011] The obtained graphene oxide solid hydrogel is vacuum dried to remove oil and water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores;
[0012] The obtained graphene oxide aerogel is reduced at high temperature to obtain a graphene aerogel with multiple pores.
[0013] Preferably, the oil phase component is a substance that is incompatible with water and has different solidification points under the same pressure, and the set volume ratio of the oil phase to the water phase is 1:1 to 1:5.
[0014] Preferably, the rotation speed of the high-speed shearing is not less than 10000 r / min, and the time is 1 to 5 min.
[0015] Preferably, the step-by-step cooling type one-way freezing specifically comprises: placing the obtained oil-in-water emulsion in a mold so that its bottom surface contacts an ultra-low temperature cold source, and performing one-way freezing.
[0016] Preferably, the mold uses insulation material to wrap the upper bottom surface and surrounding areas of the aerogel container, leaving only the lower bottom surface of the container unwrapped with insulation material, so that its bottom surface is in contact with the ultra-low temperature cold source.
[0017] Preferably, the ultra-low temperature cold source is any one of a refrigerant or a refrigeration device.
[0018] Preferably, in the one-way freezing process, the mold containing the oil-in-water emulsion is placed at a temperature below the solidification point of one phase and above the solidification point of the other phase for a set time and then placed at a temperature below the solidification point of the other phase for a set time.
[0019] Preferably, the vacuum drying pressure is 10 Pa or less, and the time is 12 hours or more;
[0020] The temperature of the high temperature reduction is 200-700°C.
[0021] The second aspect of the present invention discloses an application of the graphene aerogel prepared by the preparation method, and a method for applying the graphene aerogel with multiple pores to thermal insulation, wherein the internal pores of the graphene aerogel material are attached parallel to the surface of an object requiring thermal insulation to block heat transfer.
[0022] The third aspect of the present invention discloses an application of the graphene aerogel prepared by the preparation method. The graphene aerogel with multiple channels is applied to the method of photothermal oil absorption. Under sunlight, the internal channels of the graphene aerogel material are placed on the oil surface perpendicular to the surface of the oil. After the material absorbs light, it heats up and heats the oil, reducing the viscosity of the oil to achieve adsorption.
[0023] Compared with the prior art, the beneficial effects of the present invention include at least:
[0024] (1) The preparation method of the graphene aerogel described in the present invention is simple, low-cost, can be prepared on a large scale, and has broad application prospects.
[0025] (2) The preparation method adopted by the present invention is to shape the isotropic primary pores of the material with unstable GO-O / W emulsion droplets; then solidify one phase and then solidify the other phase by step-by-step cooling unidirectional freezing, thereby stabilizing the primary pores and promoting the directional arrangement of the primary pores to form the final multiple pores. The step-by-step cooling unidirectional freezing can make the graphene aerogel with multiple pores have an anisotropic structure. By simply adjusting the freezing temperature and the volume ratio of the oil phase to the water phase, materials with different properties can be prepared.
[0026] (3) The graphene aerogel with multiple pores of the present invention has high porosity, anisotropic thermal conductivity, good thermal insulation performance perpendicular to the pore arrangement direction, good heat transfer performance parallel to the pore arrangement direction, high adsorption rate and large adsorption amount for crude oil, and can be used as both a thermal insulation material and an adsorption material, and can be widely used in the fields of energy conservation, environmental protection, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the material preparation method of the present invention;
[0028] Figure 2 This is a SEM image of the graphene aerogel with multiple pores obtained in Example 5;
[0029] Figure 3 The graphene aerogel with multiple channels obtained in Example 5 is 2 The curve of the mass change of high viscosity oil along the ice crystal growth direction during the photothermal-oil absorption experiment under strong light;
[0030] Figure 4 The graphene aerogel with multiple channels obtained in Example 5 is 2 The time-varying curve of the upper and lower surface temperatures when adsorbing high-viscosity oil along the growth direction of ice crystals during the photothermal-oil absorption experiment under strong light.
[0031] Figure 5 This is the SEM image of the graphene aerogel with multiple channels obtained in Example 7. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The embodiments described in this application are only embodiments of a part of the present invention, rather than all embodiments. Based on the spirit of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0033] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a graphene aerogel having multiple pores, comprising the following steps:
[0034] Step 1, mixing the graphene oxide aqueous dispersion and the oil phase according to a set volume ratio, and obtaining an unstable oil-in-water (GO-O / W) emulsion after high-speed shearing;
[0035] In a preferred but non-limiting embodiment of the present invention, in step 1, the amount of graphene oxide in the graphene oxide aqueous dispersion is 0.1 to 1 part of graphene oxide per 100 parts of water, and the content of graphene oxide can be higher.
[0036] The oil phase components may be selected from alkanes, olefins, benzene and its homologues, halogenated hydrocarbons, oils, esters, higher alcohols, petroleum and other substances that are incompatible with water and have different freezing points under the same conditions.
[0037] The volume ratio of the oil phase to the water phase is 1:1-1:5, and more preferably, the volume ratio of the oil phase to the water phase is 1:1.25-1:2.5.
[0038] The high-speed shearing has a rotation speed of 10,000 r / min or above and a time of 1 to 5 min.
[0039] Step 2, freezing the GO-O / W emulsion obtained in step 1 in a step-by-step unidirectional manner, and obtaining a graphene oxide solid hydrogel by water-oil step-by-step solidification;
[0040] In step 2, the specific steps of the step-by-step cooling unidirectional freezing are: placing the GO-O / W emulsion obtained in step 1 in a mold so that its bottom surface contacts an ultra-low temperature cold source for unidirectional freezing.
[0041] The mold uses insulation material to wrap the upper bottom surface and surrounding areas of the aerogel container, leaving only the lower bottom surface of the container unwrapped with insulation material, so that only the bottom surface can contact the ultra-low temperature cold source.
[0042] The ultra-low temperature cold source is a refrigerant such as liquid carbon dioxide, liquid ammonia, liquid nitrogen, or a refrigeration device such as an ultra-low temperature refrigerator.
[0043] In the step-by-step cooling unidirectional freezing process, the sample is frozen at a temperature below the freezing point of one phase and above the freezing point of the other phase for a period of time, and then frozen at a temperature below the freezing point of the other phase for a period of time.
[0044] It is worth noting that the one phase and the other phase in this embodiment refer to the oil phase and the water phase described in step 1, but this is not the case for all experiments. The freezing order of the two phases is not fixed and depends on the freezing points of the water phase and the oil phase. When the freezing point of the selected organic matter is higher than that of water, the cooling process will show that the oil phase is frozen first and the water phase is frozen later; and when the freezing point of the organic matter is lower than that of water, the opposite order is presented. Therefore, the specific phases are not limited here, but are replaced by one phase and the other phase.
[0045] For example, when cyclohexane is selected as the oil phase component, the sample is frozen at a temperature below the freezing point of cyclohexane and above the freezing point of water (1°C) for a period of time, and then the sample is frozen at a temperature below the freezing point of water (-25 to -65°C) for a period of time.
[0046] Step 3, vacuum drying the graphene oxide solid hydrogel obtained in step 2 to remove oil and water inside and on the surface of the pores to obtain a graphene oxide aerogel with multiple pores.
[0047] In step 3, the vacuum drying pressure is 10 Pa or less, and the time is 12 hours or more.
[0048] Step 4, subjecting the graphene oxide aerogel obtained in step 3 to high-temperature reduction to obtain a graphene aerogel with multiple pores.
[0049] In step 4, high-temperature reduction is carried out in a tubular furnace, and the temperature of high-temperature reduction is 200-700°C.
[0050] By simply adjusting the freezing temperature and the volume ratio of the oil phase to the water phase, materials with different properties can be prepared. Specifically, as the freezing temperature decreases, the thermal conductivity of the material along the direction of ice crystal growth increases, the thermal conductivity perpendicular to the direction of ice crystal growth decreases, and the adsorption rate of crude oil decreases. As the volume ratio of the oil phase to the water phase increases, the thermal conductivity of the material along the direction of ice crystal growth increases, and the adsorption capacity of crude oil increases.
[0051] The present invention is based on the principle of using unstable GO-O / W emulsion droplets to shape the isotropic primary channels of the material; then using step-by-step cooling unidirectional freezing to first solidify one phase and then solidify the other phase, thereby stabilizing the primary channels and promoting the directional arrangement of the primary channels to form the final multiple channels.
[0052] Another embodiment of the present invention provides an application of a graphene aerogel with multiple channels. The graphene aerogel with multiple channels obtained based on the preparation method is applied to thermal insulation and photothermal oil absorption, specifically:
[0053] The thermal insulation method is to attach the internal channels of the graphene aerogel material parallel to the surface of the object requiring thermal insulation, thereby blocking the heat transfer.
[0054] The method of photothermal oil absorption is to place the internal channels of the graphene aerogel material on the oil surface perpendicularly to the surface of the oil under sunlight. After absorbing light, the material quickly heats up and heats the oil, reducing the viscosity of the oil to achieve rapid adsorption. At the same time, it can effectively prevent heat from dissipating from all sides, thereby improving energy utilization efficiency.
[0055] Embodiment 1:
[0056] (1) Preparation of GO-O / W emulsion
[0057] Cyclohexane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:2.5 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0058] (2) Preparation of graphene oxide solid hydrogel
[0059] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 h to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 h to obtain a graphene solid hydrogel.
[0060] (3) Preparation of graphene oxide aerogel
[0061] The graphene oxide solid hydrogel obtained in step (2) is vacuum dried at 3 Pa for 24 hours to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores.
[0062] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400° C. for 2 h to obtain a graphene aerogel with multiple pores.
[0063] (5) Thermal conductivity measurement
[0064] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.087 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.063 W / (m·K).
[0065] (6) Photothermal adsorption of crude oil applications
[0066] Under light, the graphene aerogel with multiple pores obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the growth direction of ice crystals. When the adsorption reached saturation, each gram of aerogel could adsorb 233.25 times its own mass of high-viscosity crude oil, and the adsorption rate was 11.66 g / (g·min).
[0067] Embodiment 2:
[0068] (1) Preparation of GO-O / W emulsion
[0069] Cyclohexane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:2.5 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0070] (2) Preparation of graphene oxide solid hydrogel
[0071] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 h to solidify the cyclohexane droplets inside, and then placed on a cold source at -45°C for unidirectional freezing for 1 h to obtain a graphene solid hydrogel.
[0072] (3) Preparation of graphene oxide aerogel
[0073] The graphene oxide solid hydrogel obtained in step (2) is vacuum dried at 3 Pa for 24 hours to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores.
[0074] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400° C. for 2 h to obtain a graphene aerogel with multiple pores.
[0075] (5) Thermal conductivity measurement
[0076] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.092 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.059 W / (m·K).
[0077] (6) Photothermal adsorption of crude oil applications
[0078] Under light, the graphene aerogel with multiple pores obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the growth direction of ice crystals. When the adsorption reached saturation, each gram of aerogel could adsorb 240.37 times its own mass of high-viscosity crude oil, and the adsorption rate was 10.93 g / (g·min).
[0079] Embodiment 3:
[0080] (1) Preparation of GO-O / W emulsion
[0081] Cyclohexane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:2.5 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0082] (2) Preparation of graphene oxide solid hydrogel
[0083] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 h to solidify the cyclohexane droplets inside, and then placed on a cold source at -65°C for unidirectional freezing for 1 h to obtain a graphene solid hydrogel.
[0084] (3) Preparation of graphene oxide aerogel
[0085] The graphene oxide solid hydrogel obtained in step (2) is vacuum dried at 3 Pa for 24 hours to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores.
[0086] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400° C. for 2 h to obtain a graphene aerogel with multiple pores.
[0087] (5) Thermal conductivity measurement
[0088] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.106 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.052 W / (m·K).
[0089] (6) Photothermal adsorption of crude oil applications
[0090] Under light, the graphene aerogel with multiple pores obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the growth direction of ice crystals. When the adsorption reached saturation, each gram of aerogel could adsorb 226.54 times its own mass of high-viscosity crude oil, and the adsorption rate was 9.85 g / (g·min).
[0091] Embodiment 4:
[0092] (1) Preparation of GO-O / W emulsion
[0093] Cyclohexane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:1.67 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0094] (2) Preparation of graphene oxide solid hydrogel
[0095] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 h to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 h to obtain a graphene solid hydrogel.
[0096] (3) Preparation of graphene oxide aerogel
[0097] The graphene oxide solid hydrogel obtained in step (2) is vacuum dried at 3 Pa for 24 hours to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores.
[0098] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400° C. for 2 h to obtain a graphene aerogel with multiple pores.
[0099] (5) Thermal conductivity measurement
[0100] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.094 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.061 W / (m·K).
[0101] (6) Photothermal adsorption of crude oil applications
[0102] Under light, the graphene aerogel with multiple pores obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the growth direction of ice crystals. When the adsorption reached saturation, each gram of aerogel could adsorb 238.24 times its own mass of high-viscosity crude oil, and the adsorption rate was 10.83 g / (g·min).
[0103] Embodiment 5:
[0104] (1) Preparation of GO-O / W emulsion
[0105] Cyclohexane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:1.25 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0106] (2) Preparation of graphene oxide solid hydrogel
[0107] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 h to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 h to obtain a graphene solid hydrogel.
[0108] (3) Preparation of graphene oxide aerogel
[0109] The graphene oxide solid hydrogel obtained in step (2) is vacuum dried at 3 Pa for 24 hours to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores.
[0110] (4) reducing the graphene oxide aerogel obtained in step (3) at 400° C. for 2 h to obtain a graphene aerogel having multiple pores, such as Figure 2 shown.
[0111] (5) Thermal conductivity measurement
[0112] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.115 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.076 W / (m·K).
[0113] (6) Photothermal adsorption of crude oil applications
[0114] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the direction of ice crystal growth. Figure 3 The curve of the mass of adsorbed high-viscosity oil changing with time is shown. When the adsorption reaches saturation, each gram of aerogel can adsorb 248.09 times of its own mass of high-viscosity crude oil, and the adsorption rate is 10.79g / (g·min). Figure 4 As shown, during this process, the temperature of the upper surface of the sample first increased and then decreased, while the temperature of the lower surface continued to increase.
[0115] Embodiment 6:
[0116] (1) Preparation of GO-O / W emulsion
[0117] Cyclohexane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:1.25 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0118] (2) Preparation of graphene oxide solid hydrogel
[0119] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 h to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 h to obtain a graphene solid hydrogel.
[0120] (3) Preparation of graphene oxide aerogel
[0121] The graphene oxide solid hydrogel obtained in step (2) is vacuum dried at 3 Pa for 24 hours to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores.
[0122] (4) The graphene oxide aerogel obtained in step (3) is reduced at 700° C. for 2 h to obtain a graphene aerogel with multiple pores.
[0123] (5) Thermal conductivity measurement
[0124] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.095 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.074 W / (m·K).
[0125] (6) Photothermal adsorption of crude oil applications
[0126] Under light, the graphene aerogel with multiple pores obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the growth direction of ice crystals. When the adsorption reached saturation, each gram of aerogel could adsorb 229.83 times its own mass of high-viscosity crude oil, and the adsorption rate was 11.21 g / (g·min).
[0127] Embodiment 7:
[0128] (1) Preparation of GO-O / W emulsion
[0129] n-Dodecane and graphene oxide aqueous dispersion were mixed in a volume ratio of 1:1.25 and prepared into an unstable GO-O / W emulsion after high-speed shearing.
[0130] (2) Preparation of graphene oxide solid hydrogel
[0131] The GO-O / W emulsion obtained in (1) was subjected to unidirectional freezing at -5°C for 1 h to solidify the aqueous phase, and then placed in a freezer at -25°C for 1 h to completely solidify the n-dodecane droplets to obtain a graphene solid hydrogel.
[0132] (3) Preparation of graphene oxide aerogel
[0133] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel having multiple pores, such as Figure 5 shown.
[0134] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400° C. for 2 h to obtain a graphene aerogel with multiple pores.
[0135] (5) Thermal conductivity measurement
[0136] The thermal conductivity of the graphene aerogel with multiple pores prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the direction of ice crystal growth was 0.107 W / (m·K), and the thermal conductivity perpendicular to the direction of ice crystal growth was 0.082 W / (m·K).
[0137] (6) Photothermal adsorption of crude oil applications
[0138] Under light, the graphene aerogel with multiple pores obtained in (4) was placed on the surface of crude oil (viscosity 25574.1 mPa·s at 25°C) along the growth direction of ice crystals. When the adsorption reached saturation, each gram of aerogel could adsorb 264.31 times its own mass of high-viscosity crude oil, and the adsorption rate was 9.25 g / (g·min).
[0139] Compared with the prior art, the beneficial effects of the present invention include at least:
[0140] (1) The preparation method of the graphene aerogel described in the present invention is simple, low-cost, can be prepared on a large scale, and has broad application prospects.
[0141] (2) The preparation method adopted by the present invention is to shape the isotropic primary pores of the material with unstable GO-O / W emulsion droplets; then solidify one phase and then solidify the other phase by step-by-step cooling unidirectional freezing, thereby stabilizing the primary pores and promoting the directional arrangement of the primary pores to form the final multiple pores. The step-by-step cooling unidirectional freezing can make the graphene aerogel with multiple pores have an anisotropic structure. By simply adjusting the freezing temperature and the volume ratio of the oil phase to the water phase, materials with different properties can be prepared.
[0142] (3) The graphene aerogel with multiple pores of the present invention has high porosity, anisotropic thermal conductivity, good thermal insulation performance perpendicular to the pore arrangement direction, good heat transfer performance parallel to the pore arrangement direction, high adsorption rate and large adsorption amount for crude oil, and can be used as both a thermal insulation material and an adsorption material, and can be widely used in the fields of energy conservation, environmental protection, etc.
[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents, and any modifications or equivalent replacements that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a graphene aerogel having multiple pores, characterized in that: The following steps are involved: The graphene oxide aqueous dispersion and the oil phase are mixed according to a set volume ratio, and an unstable oil-in-water emulsion is obtained after high-speed shearing; The obtained oil-in-water emulsion is subjected to step-by-step unidirectional freezing to obtain a graphene oxide solid hydrogel through step-by-step solidification of water and oil; The obtained graphene oxide solid hydrogel is vacuum dried to remove oil and water inside and on the surface of the pores, thereby obtaining a graphene oxide aerogel with multiple pores; The obtained graphene oxide aerogel is reduced at high temperature to obtain a graphene aerogel with multiple pores.
2. The method for preparing a graphene aerogel having multiple pores according to claim 1, characterized in that: The oil phase component is a substance that is incompatible with water and has different solidification points under the same pressure, and the set volume ratio of the oil phase to the water phase is 1:1 to 1:
5.
3. The method for preparing a graphene aerogel having multiple pores according to claim 1, characterized in that: The rotation speed of the high-speed shearing is not less than 10000 r / min, and the time is 1 to 5 minutes.
4. The method for preparing a graphene aerogel having multiple pores according to claim 1, characterized in that: The step-by-step cooling type one-way freezing specifically comprises: placing the obtained oil-in-water emulsion in a mold, making its bottom surface contact with an ultra-low temperature cold source, and performing one-way freezing.
5. The method for preparing a graphene aerogel having multiple pores according to claim 4, characterized in that: The mold uses insulation material to wrap the upper bottom surface and surroundings of the aerogel container, leaving only the lower bottom surface of the container unwrapped with insulation material, so that the bottom surface is in contact with the ultra-low temperature cold source.
6. The method for preparing a graphene aerogel having multiple pores according to claim 4, characterized in that: The ultra-low temperature cold source is any one of a refrigerant or a refrigeration device.
7. The method for preparing a graphene aerogel having multiple pores according to claim 4, characterized in that: In the one-way freezing process, a mold containing an oil-in-water emulsion is placed at a temperature below the solidification point of one phase and above the solidification point of the other phase for a set time, and then placed at a temperature below the solidification point of the other phase for a set time.
8. The method for preparing a graphene aerogel having multiple pores according to claim 1, characterized in that: The vacuum drying pressure is 10Pa or less, and the time is 12 hours or more; The temperature of the high temperature reduction is 200-700°C.
9. An application of the graphene aerogel prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The method for applying the graphene aerogel with multiple pores to thermal insulation is to attach the internal pores of the graphene aerogel material parallel to the surface of an object requiring thermal insulation to block heat transfer.
10. An application of the graphene aerogel prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The method of applying the graphene aerogel with multiple pores to photothermal oil absorption is that the internal pores of the graphene aerogel material are placed on the oil surface perpendicular to the surface of the oil under sunlight. After the material absorbs light, it heats up and heats the oil, reducing the viscosity of the oil to achieve adsorption.
Citation Information
Patent Citations
Preparation method of graphene aerogel on basis of emulsion method
CN107226464A
Graphene composite aerogel preparation method
CN107732215A
Graphene-based aerogel with asymmetric wettability and preparation method and application thereof
CN109081331A
Preparing method of aperture-adjustable graphene aerogel
CN109133040A
All-carbon graphene aerogel and preparation method thereof
CN110562964A